How science works : evaluating evidence in biology and medicine - Jenkins, Stephen H. (Oxford University Press, 2004)
One week, red wine is good for the heart. The next week, new reports say it's bad for the health. So which is true? Anyone who's ever read science news with fascination, or who's ever been confounded by conflicting stories will appreciate this book. Taking a look at some true-to-life contemporary news stories, the author assesses recent studies on topics, ranging from vitamin C and caffeine to pollution and cancer. With straight talk and a passion for the whole project of science, he demystifies the cult of the expert and sheds light on the nitty-gritty details of scientific processes. Any scientist loves a challenge, but the biggest challenge of all, observes Jenkins, is shared by scientists and nonscientitsts alike: how to make practical decisions in light of ambiguous evidence. Promising no simple answers, this book does offer excellent food for thought for people pondering that next glass of wine